Hydrodynamic properties of porcine bestrophin-1 in Triton X-100 - Stanton, J. Brett (2006)
Bestrophin-1 (Best-1) is an integral membrane protein, defects in which cause Best vitelliform macular dystrophy. Best-1 is proposed to function as a Cl(−) channel and/or a regulator of Ca(++) channels. A tetrameric (or pentameric) stoichiometry has been reported for recombinant best-1. Using a combination of gel exclusion chromatography and velocity sedimentation we examined the quaternary structure of native best-1 and found that it migrates as a single species with a Stokes radius of 7.3 nm, sedimentation coefficient (S(20,w)) of 4.9, and partial specific volume (ν) of 0.80 ml/g. The mass of the protein–detergent complex is calculated to be 206 kDa, with the protein component estimated to be ~138 kDa. Given a monomeric mass of 68 kDa, we conclude that native best-1 solubilized with Triton X-100 is a homodimer. The differences between this observation and a prior report were examined by comparing recombinant best-1 with tissue derived best-1 using gel exclusion chromatography. Much of the recombinant best-1 eluted in the column void (V(o)) fraction, unlike that extracted from RPE cells. We conclude that the minimal functional unit of best-1 is dimeric. This stoichiometry differs from that previously measured for recombinant best-1, suggesting that further studies are necessary to determine the stoichiometry of functional best-1 in RPE membranes.